Comparisons of pharmacokinetics and genetic polymorphisms between type 2 diabetic patients with and without edema conditions when treated with thiazolidinediones - Wannakamol Sonsingh (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2008